THE DEVELOPMENT OF TRAINING MODEL FOR ADMINISTRATIVE LEADERSHIP COMPETENCE BASED ON ACTION-BASED LEARNING IN UNIVERSITY - Sulastri Sulastri; Nurhizrah Gistituati; Neviyarni S; Hasdi Aimon (Universitas Gadjah Mada, 2021)
Introduction/Main Objectives: This research is motivated by the findings of the preliminary research conducted at the administrative leaders at Universitas Negeri Padang. Background Problems: Less optimal leadership competency in administrative leadership in terms of change management, conflict management, communication, decision making, team building, and the ability to improve performance. Novelty: This model can support any program and support the expansion of the master program and/or development of the doctoral level in leadership and management of higher education, especially for the development of the capacity of structural leaders. Furthermore, this model has a very large contribution also to increase the capacity building of universities. In addition, this model can be used as the basis for opening a special study program for leaders, in increasing their leadership competence. Research Methods: This research is a development research using ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. In accordance with the results of preliminary research that has been done, then the model is developed through a process of self-evaluation, Focus Group Discussion (FGD), one to one trial and small group testing and large group testing. Research data were collected using a questionnaire, observation, and a questionnaire. The collected data is analyzed using descriptive statistics and inferential statistics. Finding/Results: This study produced 4 (four) products, namely model book, material book, instructor guidebook and participant guidebook. These products were declared to be very valid by experts both in terms of construction, content and linguistic aspects so that they were suitable for use. Practicality test results show that it is very practical for the four products that have been developed.Conclusion: Furthermore, this model has a very large contribution also to increase the capacity building of universities.